2001
DOI: 10.1128/iai.69.1.237-244.2001
|View full text |Cite
|
Sign up to set email alerts
|

Human T- and B-Cell Responses toSchistosoma mansoniRecombinant Glyceraldehyde 3-Phosphate Dehydrogenase Correlate with Resistance to Reinfection withS. mansoniorSchistosoma haematobiumafter Chemotherapy

Abstract: Recently we reported that human T-and B-cell recognition of a 42-kDa protein (p42) in soluble extracts of adult Schistosoma mansoni worms correlates with resistance to reinfection with S. mansoni or S. haematobium. Amino acid microsequencing of p42 revealed that it consists predominantly of schistosome glyceraldehyde 3-phosphate dehydrogenase (SG3PDH). We have expressed SG3PDH in Escherichia coli and purified the recombinant protein in a soluble and enzymatically active form. Recombinant SG3PDH (rSG3PDH) react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
44
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 39 publications
6
44
0
Order By: Relevance
“…Heparinized whole blood was diluted 1:4 in Roswell Park Memorial Institute (RPMI) -1640 medium supplemented with 200 units/mL penicillin, 200 μg/mL streptomycin, 50 ng/mL amphotericin, and 20 μg/mL polymyxin B (Sigma-Aldrich) as an inhibitor of any residual lipopolysaccharide contamination of antigen; 200 μL diluted blood was incubated in duplicate with 50 μL medium containing 0 or 40 μg/mL recombinant S. mansoni glyceraldehyde 3-phosphate dehydrogenase (rSG3PDH) prepared as described previously. 35 Whole-blood cultures were incubated for 72 hours at 37 C and 3% CO 2 and then centrifuged at 400 + g for 10 minutes. The cell-free supernatants were transferred into wells of sterile plates and stored at −76 C until assayed by capture ELISA for levels of released IL-4, IL-17, and IFN-γ (BioLegend) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Heparinized whole blood was diluted 1:4 in Roswell Park Memorial Institute (RPMI) -1640 medium supplemented with 200 units/mL penicillin, 200 μg/mL streptomycin, 50 ng/mL amphotericin, and 20 μg/mL polymyxin B (Sigma-Aldrich) as an inhibitor of any residual lipopolysaccharide contamination of antigen; 200 μL diluted blood was incubated in duplicate with 50 μL medium containing 0 or 40 μg/mL recombinant S. mansoni glyceraldehyde 3-phosphate dehydrogenase (rSG3PDH) prepared as described previously. 35 Whole-blood cultures were incubated for 72 hours at 37 C and 3% CO 2 and then centrifuged at 400 + g for 10 minutes. The cell-free supernatants were transferred into wells of sterile plates and stored at −76 C until assayed by capture ELISA for levels of released IL-4, IL-17, and IFN-γ (BioLegend) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…It was recently shown that a 42 kDa soluble adult worm antigen band, identified as S. mansoni glyceraldehyde 3-phosphate dehydrogenase (SG3PDH), is a target of cellular and humoral immune responses in subjects resistant to infection with schistosomes [7,8]. Additionally, several schistosomular and adult worm antigens were detected by sera from mice immunized with radiation-attenuated cercariae (RA), among which Sm23, glutathione S-transferase, triose phosphate isomerase, Sm32, heat shock protein, calreticulin, and paramyosin are the best studied [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The coding sequence for SG3PDH was obtained and expressed, and the recombinant protein (rSG3PDH) was purified by metal affinity chromatography (HiTrap TM Affinity Column, Pharmacia) as detailed previously (El Ridi et al 2001b). Antigen aliquots were kept until use at -76°C and thawed only once.…”
Section: Methodsmentioning
confidence: 99%